Concentrations Of Heavy Metals In Leafy Vegetables Taken From A Local Market In Kundra, Koraput, Odisha, India (Journal of Pharmaceutical Negative Results, 2023)
Plants are the major source of energy for humans. Leafy vegetables are rich sources of nutrients, fibers, minerals and trace elements which help in treatment of diseases and maintaining good health. However heavy metal contamination due to environmental pollution results in poisonous and hazardous effects. This study is based on the concentration of heavy metals in leafy vegetables in a village named Kundra located in district Koraput, 42 kilometers from Koraput of Odisha, India, which has a population of about 5326.About 130 samples were examined and studied from the local market of Kundra. These leafy vegetables commonly called Lal bhaji sago (Red Spinach), Muniga Sago (Drumstick Leaves) and Methi sago (Fenugeek leaves) were used for this study. The samples were cut air dried for four days. Next it was washed in 20% v/v solution of nitric acid, dried sample was then grounded into powder, it was sieved through nylon sieve of size 2mm. The digestion of the sample involves 20 ml of concentrated nitric acid, perchloric acid, and hydrochloric acid in the ratio of 10:1:3, followed by drying at 105 degree Celsius on a hot plate. The obtained solution was than filtered, the residue was than analyzed using digital spectrophotometer by continuous dilution method. The concentration of Iron, copper and zinc was determined, which constituted below permissible limit according to World Health Organization. Monitoring heavy metals in vegetables is essential; as these are considered to be a major indicator of environmental pollution.